COMPARISON OF RUGA PALATAL PATTERNS BETWEEN LYSELL METHOD AND THOMAS KOTZE METHOD FOR GENDER IDENTIFICATION IN BETAWI ETHNICITY - Nathalie stella; Moch Atmaji Windrianto; Okky Marita Ardy; Siti Nur Riani (YARSI Dental Scientific Meeting - e Journal, 2025)
Background: Forensic identification is an important aspect of dental science, especially in revealing individual identities through ruga palatal patterns. This study compares two main methods of gender identification based on ruga palatal patterns, namely the Lysell method and the Thomas Kotze method, within the Betawi ethnic community. Objective: To determine the differences in palatal rugae patterns between the Lysell method and the Thomas-Kotze method for sex identification in the Betawi ethnic group. Methods: This study is quantitative with a descriptive statistical analysis approach. The sample consists of 25 males and 25 females who are individuals from the Betawi ethnic group with certain inclusion criteria. Data were collected through ruga palatal printing, then analyzed using both classification methods. Statistical analysis was conducted to assess the significance of pattern differences based on gender. Results: There was no difference in the pattern of ruga palatal between men and women, both using the Lysell method and the Thomas Kotze method. Conclusion: The ruga palatal pattern can be used as a tool for sex identification, with the methods of Thomas Kotze and Lysell each having their own advantages in pattern classification. In Islam, the use of forensic science for the purposes of identification and justice aligns with the principle of protecting individual rights and human dignity.